Pengembangan Buku Interaktif Layanan Lembaga Keuangan Syariah Berbasis Scientific Approach Di SMK - Evi Ayu Retnosari; Luqman Hakim (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2020)
The developmet technology and information in education present various form of text books. Research as aimed to explain the development interactive book and effectiviness of the used of the book. The final results of this research are produces interative book based on scientific approach sharia financial institution services that can used by student. The research prosedure in the Four D model by Thiagarajan Semmel and Semmel. Which are performed in a complete maner with out excluding a single stage. The instrumens of data included open questionnaries and closes qustionnaries. The results of the due diligence carried out by expert, explained with verry decent that the product can be used apllied as a source of learning in this subject. The trials was carried out in a limited manner with a sample of 20 students who cme from SMK Negeri 1 Lamongan XII class majoring in Islamic Banking giving very positive kriteri to the product being developed.